Store-Operated Calcium Channels as Drug Target in Gastroesophageal Cancers - Chang, Yan; Roy, Souvik; Pan, Zui (Frontiers in Pharmacology, 2021)
Gastroesophageal cancers, including tumors occurring in esophagus and stomach, usually have poor prognosis and lack effective chemotherapeutic drugs. The association between dysregulated store-operated calcium entry (SOCE), a key intracellular Ca2+ signaling pathway and gastroesophageal cancers is emerging. This review summarizes the recent advances in understanding the contribution of SOCE-mediated intracellular Ca2+ signaling to gastroesophageal cancers. It assesses the pathophysiological role of each components in SOCE machinery, such as Orais and STIMs in the cancer cell proliferation, migration, and invasion as well as stemness maintainese. Lastly, it discusses efforts towards development of more specific and potent SOCE inhibitors, which may be a new set of chemotherapeutic drugs appearing at the horizon to provide either targeted therapy or neoadjuvant treatment to overcome drug resistant for gastroesophageal cancers.